Early Detection of Disseminated Intravascular Coagulation During Septic Shock: A Multicenter Prospective Study. Issue 10 (October 2016) - Delabranche, Xavier; Quenot, Jean-Pierre; Lavigne, Thierry; Mercier, Emmanuelle; François, Bruno; Severac, François; Grunebaum, Lélia; Mehdi, Madah; Zobairi, Fatiha; Toti, Florence; Meziani, Ferhat; Boisramé-Helms, Julie
Abstract : Objectives: Inadequate stratification of septic shock patients may result in inappropriate treatment allocation in randomized clinical trials, especially regarding anticoagulant. We previously reported that endothelial-derived microparticles are relevant biomarkers of sepsis-induced disseminated intravascular coagulation. In this validation cohort, we assess microparticles as surrogates of cell activation to improve early disseminated intravascular coagulation diagnosis and patient stratification. Design: Prospective observational study in septic shock patients. Settings: Four medical ICUs in university hospitals. Patients and Methods: Two hundred sixty-five patients with septic shock from four ICUs were consecutively enrolled. Disseminated intravascular coagulation was diagnosed according to Japanese Association for Acute Medicine 2006 score. Endothelial- and leukocyte-derived circulating procoagulant microparticles were isolated and quantified by prothrombinase assay at admission, day 3, and day 7. Intervention: None. Measurements and Main Results: Two hundred fifty-nine patients were analyzed. Sixty-one had disseminated intravascular coagulation at admission, and 32 developed disseminated intravascular coagulation during the first 24 hours after admission. Multiple logistic regression model confirmed that endothelial cell-derived microparticles were associated with disseminated intravascular coagulation: CD105 + -microparticles (odds ratio, 2.13) and CD31 + -microparticles (odds ratio, 0.65) ( p < 0.05). Furthermore, CD11a + -microparticles to leukocyte ratio evidenced leukocyte activation (odds ratio, 1.59; p < 0.05). Prediction of disseminated intravascular coagulation was also analyzed after exclusion of patients with disseminated intravascular coagulation at admission. A new multiple logistic regression analysis demonstrated the association of CD105 + -microparticles (> 0.60 nM eq. PhtdSer; odds ratio, 1.67; p < 0.01), platelets count (⩽ 127 g/L; odds ratio, 0.99; p < 0.01), and prothrombin time (⩽ 58%; odds ratio, 0.98; p < 0.05) with disseminated intravascular coagulation. A combining score at admission is predictive of the absence of disseminated intravascular coagulation (area under the curve, 72.9%; specificity, 71.2%; sensitivity, 71.0%, with a negative predictive value of 93.1% and a positive predictive value of 31.0%). Conclusions: Procoagulant microparticles from endothelial cells and leukocytes reflect a vascular injury during sepsis-induced disseminated intravascular coagulation that precedes obvious activation of coagulation. A combination of prothrombin time, endothelium-derived CD105 + -microparticles, and platelet count at admission could predict the absence of disseminated intravascular coagulation and allow a better stratification in future randomized clinical trials.